Rubin's Pathology: Clinicopathologic Foundations of Medicine - Raphael Rubin (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
The highly acclaimed foundation textbook Rubin\\\\\\\'s Pathology: Clinicopathologic Foundations of Medicine, now in its Sixth Edition, provides medical students with a lucid discussion of basic disease processes and their effects on cells, organs, and people. The streamlined coverage includes only what medical students need to know and provides clinical application of the chapter concepts. Icons signal discussions of pathogenesis, pathology, epidemiology, etiological factors, and clinical features. Rubin\\\\\\\'s Pathology is liberally illustrated with full-color graphic illustrations, gross pathology photos, and micrographs. The Sixth Edition is completely updated with expanded and revised content. A suite of exciting online tools for students includes a fully searchable e-text with all images, 140 interactive case studies, 1500 audio review questions, summary podcast lectures, and a selection of mobile flash cards for iPhone, iPod, and BlackBerry from the new Rubin\\\\\\\'s Pathology Mobile Flash Cards. Resources for faculty include a 600 question test generator and chapter outlines and objectives.